Automatic creating variation of CS1 assignments and exams - Pereira, Filipe Dwan; Júnior, Hermino Barbosa de Freitas; Oliveira, Elaine Harada Teixeira de; Carvalho, Leandro Silva Galvão de; Oliveira, David Braga Fernandes de; Benedict, Aileen; Dorodchi, Mohsen; Cristea, Alexandra Ioana (Anais Estendidos do Simpósio Brasileiro de Educação em Computação (EDUCOMP); 2021: Anais Estendidos do I Simpósio Brasileiro de Educação em ComputaçãoDO - 10.5753/educomp_estendido.2021.14856, 2021)
The adoption of Online Judge (OJ) environments by CS1 instructors has increased over the last few years. A potential explanation of this growth is that OJs reduce instructors? workload in correcting learners? codes and provide instantaneous and accurate feedback to students about the correctness of their solutions. Despite the benefits, there are still repetitive and laborious tasks to feed OJ systems. For example, the literature recommends that instructors create variations of assignments and exams for different CS1 classes during the semesters to hamper plagiarism practice. By creating variations of assignments and exams, it is more difficult for students to use code solutions from past courses. To address this, we intend to create a mechanism for automatically selecting problems to compose new assignments and exams so that the new selection of problems is similar enough to the old in terms of problem topics and challenge levels. A video explaining this work can be found at the following link: https://youtu.be/ANqMD-ZAURk .